Substitution of telemedicine for clinic visit during the COVID‐19 pandemic of 2020: Comparison of telemedicine and clinic visit. Issue 9 (25th May 2022) - Onishi, Yukiko; Ichihashi, Rieko; Yoshida, Yoko; Tahara, Tazu; Kikuchi, Takako; Kobori, Toshiko; Kubota, Tetsuya; Iwamoto, Masahiko; Hamano, Shoko; Kasuga, Masato
ABSTRACT: Aims/Introduction: The purpose of this retrospective observational cohort study was to compare outpatient diabetes care and glycated hemoglobin (HbA1c) level during the coronavirus disease 2019 pandemic in 2020 with 2019, and to compare the glucose‐lowering effect of telemedicine and clinic visits during the state of emergency in Japan declared from 7 April to 25 May (inter‐period) 2020. Materials and Methods: A total of 13 weeks before and after the inter‐period were designated as the pre‐period and post‐period, respectively. The number of study participants who had clinic visits during the pre‐period and the post‐period were 3, 333 in 2020 and 3, 608 in 2019. Propensity score matching was carried out to compare the effect of telemedicine and clinic visits on diabetes control in 2020 among diabetes patients with insufficient glucose control (HbA1c ≥7%). The primary outcome was post‐period HbA1c. Results: The major difference between 2020 and 2019 was the use of telemedicine in 2020. After adjustment for age, sex, diabetes type, pre‐period HbA1c and pre‐period body mass index, glycemic control evaluated by HbA1c was significantly worse in the post‐period of 2020 than 2019. In the propensity score‐matched 618 pairs, the clinic visit group had significantly better post‐period HbA1c than the telemedicine group (7.5% vs 7.4%, P  = 0.023). Conclusions: Glycemic control was slightly, but significantly, worse in 2020 than 2019. Although telemedicine significantly improved glycemic control during the coronavirus disease 2019 pandemic in 2020, clinic visits improved HbA1c significantly more. The substitution of telemedicine for clinic visits appears to be a viable option under emergency conditions, but clinic visits might be a better option when possible. Abstract : Glycemic control was slightly worse in 2020 than 2019. Although telemedicine significantly improved glycemic control during the COVID‐19 pandemic in 2020, clinic visit improved HbA1c significantly more. Whether this difference is clinically significant is uncertain and although clinic visit may be a better option when possible, substitution of telemedicine for clinic visit appears to be a viable option.